Esophagogastroduodenoscopy findings in patients with dyspepsia - Vasiljević, Ivana; Lukić, Snežana (Medical Research, 2024)
Introduction/Aim: Dyspepsia is a set of symptoms of the gastrointestinal tract that includes epigastric pain or burning, postprandial fullness or early satiety. These symptoms may or may not be associated with pathological changes in the mucosa. Esophagogastroduodenoscopy (EGD) is an invasive diagnostic tool for detecting pathological changes in the mucosa of the upper digestive tract.The aim of this study is to detect how many patients with dyspepsia older than 55 years who underwent esophagogastroduodenoscopy had a pathological finding and determine the validity of invasive diagnostics in patients with dyspepsia.Material and methods: This cross-sectional study included 148 patients who underwent EGD in the period from June to December 2021 due to various indications (dyspepsia, vomiting, anemia, positive fecal occult blood test (FOBT), suspected portal hypertension, body weight loss, reflux disorders and melena) of which we considered only dyspepsia in patients older than 55 years.Results: In the group of patients over 55 years with dyspepsia (n = 61), 8 patients (13.1%) had a normal finding of EGD, defined as the absence of endoscopic and pathohistological changes in the mucosa. One patient (1.6%) had a normal EGD finding, with the presence of Helicobacter pylori. As for pathological endoscopic findings 24 (39.3%) patients had chronic gastritis and 13 (21.3%) chronic gastritis in the presence of H. pylori, 19 (31.1%) had signs of gastroesophageal reflux disease (GERD) and 3 (4.9%) had gastric ulcer. The presence of alarming symptoms was detected in 22.9% of patients, however, the findings of upper endoscopy ruled out the existence of gastric cancer.Conclusion: Based on our results, we can conclude that in patients with dyspepsia older than 55 years, pathological findings on EGD occur with high frequency, which proves that the benefit of using this diagnostic method is great, but the possibility of a successful empirical therapy should be also taken into account.
Keywords: esophagogastroduodenoscopy, dyspepsia, functional dyspepsia